If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -15 = 6p Reorder the terms: -15 + 3p = 6p Solving -15 + 3p = 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -15 + 3p + -6p = 6p + -6p Combine like terms: 3p + -6p = -3p -15 + -3p = 6p + -6p Combine like terms: 6p + -6p = 0 -15 + -3p = 0 Add '15' to each side of the equation. -15 + 15 + -3p = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -3p = 0 + 15 -3p = 0 + 15 Combine like terms: 0 + 15 = 15 -3p = 15 Divide each side by '-3'. p = -5 Simplifying p = -5
| 2.4x+34.4=2.9-8.1x | | 25x^2-85x+81=0 | | x+x*0.07=100 | | x-401.94=144.23 | | 3y+9=2y-7 | | k=5x^6 | | 6x+7=4x+31 | | 4p+14=-14 | | x+62=223 | | (6a^4+2a+6-a^2)-(7a-6a^3+3a^2-5a-6a-6)= | | 7x+5=4x+44 | | 6x^2=18x-12 | | -8i(-6i+2)+7(-2+6i)=0 | | 6A+8=5A-5 | | 5w-16=3w | | 180=3y-6 | | 6.2+1.4n=2.28 | | 10y^7+32y^6+6y^5=0 | | 0.16x+0.2(x-5)=0.01(4x-3) | | 15-4(2x+5y)=0 | | 36t^2+60t+25= | | 5x(3+8)=121 | | 4(x+8)-7x=2 | | y-8=-x-y | | 3ln(2)=ln(8) | | t/11=11 | | -1=1/3v | | r^2-4r+6=0 | | 2a+3c-8c+5a= | | 9-8x-7-4x=5 | | 5(4x+9)-6x=8x+12 | | 253+c=-24 |